Experimental confirmation of long hyperbolic polariton lifetimes in monoisotopic (10B) hexagonal boron nitride at room temperature - Georges Pavlidis; Jeffrey J. Schwartz; Joseph Matson; Thomas Folland; Song Liu; James H. Edgar; Josh D. Caldwell; Andrea Centrone (APL Materials, 2021)
Hyperbolic phonon polaritons (HPhPs) enable strong confinements, low losses, and intrinsic beam steering capabilities determined by the refractive index anisotropy—providing opportunities from hyperlensing to flat optics and other applications. Here, two scanning-probe techniques, photothermal induced resonance (PTIR) and scattering-type scanning near-field optical microscopy (s-SNOM), are used to map infrared (6.4–7.4 µm) HPhPs in large (up to 120 × 250 µm2) near-monoisotopic (>99% 10B) hexagonal boron nitride (hBN) flakes. Wide (≈40 µm) PTIR and s-SNOM scans on such large flakes avoid interference from polaritons launched from different asperities (edges, folds, surface defects, etc.) and together with Fourier analyses (0.05 µm−1 resolution) enable precise measurements of HPhP lifetimes (up to ≈4.2 ps) and propagation lengths (up to ≈25 and ≈17 µm for the first- and second-order branches, respectively). With respect to naturally abundant hBN, we report an eightfold improved, record-high (for hBN) propagating figure of merit (i.e., with both high confinement and long lifetime) in ≈99% 10B hBN, achieving, finally, theoretically predicted values. We show that wide near-field scans critically enable accurate estimates of the polaritons’ lifetimes and propagation lengths and that the incidence angle of light, with respect to both the sample plane and the flake edge, needs to be considered to extract correctly the dispersion relation from the near-field polaritons maps. Overall, the measurements and data analyses employed here elucidate details pertaining to polaritons’ propagation in isotopically enriched hBN and pave the way for developing high-performance HPhP-based devices.